2018
DOI: 10.1292/jvms.18-0014
|View full text |Cite
|
Sign up to set email alerts
|

Peripubertal exposure to the neonicotinoid pesticide dinotefuran affects dopaminergic neurons and causes hyperactivity in male mice

Abstract: Although neonicotinoid pesticides are expected to have harmful influence on mammals, there is little animal experimental data to support the effect and mechanisms. Since acetylcholine causes the release of dopamine, neonicotinoids may confer a risk of developmental disorders via a disturbance in the monoamine systems. Male mice were peripubertally administered dinotefuran (DIN) referring to no observed effect level (NOEL) and performed behavioral and immunohistological analyses. In an open field test, the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…However, several studies have reported the disappearance and mass death of honeybees in Europe, as well as in America and other countries, occurring since the 1990s [18,21,65], which has raised concerns about the secondary effects of these agents on non-targeted insects. It has also recently been reported that NNs have adverse effects on vertebrates for example, on the reproductive organs in reptiles [9], birds [26,60] and mammals [67], and the emotional behavior in mice [23,24,59,68]. In order to assess the risk of NNs, therefore, there is an urgent need for definitive information about their effects on mammals.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported the disappearance and mass death of honeybees in Europe, as well as in America and other countries, occurring since the 1990s [18,21,65], which has raised concerns about the secondary effects of these agents on non-targeted insects. It has also recently been reported that NNs have adverse effects on vertebrates for example, on the reproductive organs in reptiles [9], birds [26,60] and mammals [67], and the emotional behavior in mice [23,24,59,68]. In order to assess the risk of NNs, therefore, there is an urgent need for definitive information about their effects on mammals.…”
Section: Introductionmentioning
confidence: 99%
“…NNs have a higher affinity for insect nicotinic acetylcholine receptors (nAChRs) than mammal nAChRs [ 29 ] and were originally considered safe for mammals. However, in the last decade it has been reported that NNs have nicotine-like excitatory effects on mammalian nAChRs [ 13 ], especially clothianidin (CLO), a type of NN, has been reported to be toxic to mammalian emotional behavior even at less than the no-observed-adverse-effect level (NOAEL) [ 8 , 9 , 26 , 27 , 33 ]. Recent studies have also reported that NNs were detected in the urine and breast milk of pregnant women and newborns [ 2 , 10 , 15 ], and Ohno et al .…”
mentioning
confidence: 99%
“…NNs bind more readily to insect nAChRs than to mammalian nAChRs [ 38 ]. However, recent studies have reported reproductive toxicity [ 15 ] and neurobehavioral effects [ 16 , 34 , 35 , 45 ] in mammals. In terms of reproductive toxicity, it has been shown that the NN clothianidin (CLO), causes the DNA fragmentation of germ cells and the inhibition of embryonic development in mature quail [ 18 , 19 , 37 ].…”
mentioning
confidence: 99%